Lesson from COVID-19: restructuring the current health system and policies in Nepal - Subedi, Madhusudan; Subedi, Prativa (Applied Science and Technology Annals, 2020)
Although COVID-19 pandemic has created a state of alarm worldwide, the downfall in health and economy is rather paramount in low income countries. Nepal, due to its inadequate health resources and poor health system, is more vulnerable to the plight. But on a positive note, the weaknesses that have been exposed can be taken as lessons to learn. With the policies committed to achieving health as the fundamental right of people as per the constitution, capacity building, intersectoral coordination, preventive, promotive and curative facilities, and appropriate strategies and preparedness plan, Nepal can combat the pandemic and develop a resilient and well-functioning health system in future. Now is a moment of historic opportunity. Public health program must be strengthened as soon as possible by ensuring that at least minimum requirement are in place at the province and municipality levels and media partnership should be created to prevent societal fear. Furthermore, this is an opportunity to implement the power devolution in federal republic of Nepal